ANALYZING THE CONSUMER ACCEPTANCE OF MOBILE WALLET SERVICE IN MANADO (CASE STUDY OF TELKOMSEL T-CASH TAP) - Widono, Angie Michelle; Lambey, Linda .; Worang, Frederick G. (Universitas Sam Ratulangi, 2018)
Abstract: Mobile wallet is one of the recent innovation technologies invented to be an electronic financial service where people can use it as a payment method. Its ease of use is what makes people start to shift from the old payment method to the newest option of payment. One of the examples is Telkomsel T-Cash TAP. The purpose of this study is to know the consumer acceptance of mobile wallet service in Manado with a case study of Telkomsel T-Cash TAP. This research uses an exploratory approach with in-depth interviews to collect data from ten informants. Respondents were chosen by purposive sampling. The results indicate that sales promotions and ease of use have significant impact on mobile wallet service acceptance in Manado and also show that further information about the mobile wallet service, cooperation with more businesses, and easier top up methods are major concerns for the consumers to accept and adopt a mobile wallet service. It is suggested for mobile wallet services to focus on other regions and provide the users with information and knowledge regarding the top up methods as well as cooperate with other merchants in Manado to attract new consumers.Keywords: consumer acceptance, electronic payment, mobile wallet service